The role of atrial natriuretic peptide in ameliorating high altitude pulmonary edema - Irwin, David Charles, author; Bowen, R. A., advisor; Tucker, Alan, advisor; Miller, Charles W., committee member; Tissot-Van-Patot, Martha, committee member; Monnet, Eric, committee member; Roach, Rob, committee member; Klopp, Lisa, committee member (Colorado State University. Libraries, 2004)
Atrial natriuretic peptide (ANP) can reduce high altitude pulmonary edema (HAPE), but no explanation of a mechanism has been offered other than its vasodilatory and natriuretic actions. Therefore, we sought to determine if ANP could inhibit HAPE by superceding the counteracting actions of endothelin-1 (ET-1) in neutral endopeptidase (NEP) gene deficient mice and inhibit vascular leak in pulmonary endothelial cells. Plasma ANP and ET-1 concentrations, right ventricular pressure (PRV) and indices of lung injury were measured in wild type (NEP +/+) mice and mice in which the NEP gene was deleted (NEP -/-) on the same genetic background (C57BL/6J). Mice were exposed to a simulated altitude (HA) of 22,000 ft (6728 m; PB= 328 mm Hg) for 24 h. At HA lung wet weight-to-body weight increased in all animals, but greatest in the NEP (+/+) mice. Vascular leak as measured by Evans blue dye was increased only in the NEP (+/+) mice at HA. PRV was lower in NEP (-/-) mice at LA, but increased in both genotypes at HA. Plasma ANP concentrations increased at HA, but plasma ET-1 concentrations were elevated only in the NEP (-/-) mice at HA. There were negative correlations between plasma ANP concentration, lung wet weight-to-body weight and PRV. We conclude that NEP (-/-) mice showed increased ANP concentration and decreased pulmonary vascular pressure at HA, preventing HAPE. Bovine pulmonary microvascular (MVEC) and macrovascular (LEC) endothelial cell monolayers were stimulated with hypoxia, TNF-α or bacterial endotoxin (LPS) in the presence or absence of ANP, and albumin flux, NF-kb activation, TNF-α secretion, p38 MAPK and F-actin formation were assessed. In transwell cultures ANP reduced hypoxia-induced permeability in MVEC and TNF-α-induced permeability in MVEC and LEC. ANP inhibited hypoxia and LPS increased NF-kb activation and TNF-α synthesis in MVEC and LEC. Hypoxia decreased activation of p38 MAPK in MVEC, but increased activation of p38 MAPK and stress fiber formation in LEC. TNF-α had the opposite effect. ANP inhibited an activation of p38 MAPK in MVEC or LEC. These data indicate ANP has a direct cytoprotective affect on the pulmonary endothelium other then its vasodilatory and natriuretic properties.
Keywords: biochemistry; anatomy and physiology; animals